FORMATION OF COMMUNICATIVE GRAMMATICAL SKILLS IN ENGLISH LESSONS AT THE PRIMARY EDUCATION STAGE (BASED ON THE “GUESS WHAT 4” COURSEBOOK) - Zebiniso Tulkinova; Sabirova Diana Rustamovna (Uzbekistan Open Conference, 2026)
This article examines the process of developing communicative grammatical skills among primary school students in English language lessons. It highlights the importance of the communicative approach as one of the leading directions in modern language education, focused on the practical use of grammatical structures in real communication. Special attention is given to the use of the “Guess What 4” coursebook as an effective tool for developing grammatical competence within a communicative teaching context.
Keywords: communicative approach; grammatical skills; primary education; English language; Guess What 4; communicative exercises; teaching methodology